2007
DOI: 10.1002/ajmg.a.31776
|View full text |Cite
|
Sign up to set email alerts
|

A 2‐Mb critical region implicated in the microcephaly associated with terminal 1q deletion syndrome

Abstract: Patients with distal deletions of chromosome 1q have a recognizable syndrome that includes microcephaly, hypoplasia or agenesis of the corpus callosum, and psychomotor retardation. Although these symptoms have been attributed to deletions of 1q42-1q44, the minimal chromosomal region involved has not been identified. Using microsatellite and single nucleotide polymorphism (SNP) markers, we have mapped the deleted regions in seven patients with terminal deletions of chromosome 1q to define a 2.0-Mb microcephaly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 23 publications
8
71
1
Order By: Relevance
“…Critically, loss of RP58 in the CNS leads to a novel postnatal small-brain phenotype with loss of corpus callosum and cerebellar vermis hypoplasia, which resembles the human microencephaly phenotype linked to loss of chromosome-1qter. [9][10][11][12] Defective organization of the cerebral cortex in RP58 mutants. In order to confirm and extend the reported localization of RP58 in the mouse brain 15 and to interpret correctly the phenotypes described above, we performed antisense RNA in situ hybridization analyses on sections of mouse brains at different stages of development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, loss of RP58 in the CNS leads to a novel postnatal small-brain phenotype with loss of corpus callosum and cerebellar vermis hypoplasia, which resembles the human microencephaly phenotype linked to loss of chromosome-1qter. [9][10][11][12] Defective organization of the cerebral cortex in RP58 mutants. In order to confirm and extend the reported localization of RP58 in the mouse brain 15 and to interpret correctly the phenotypes described above, we performed antisense RNA in situ hybridization analyses on sections of mouse brains at different stages of development.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, deletion of the distal end of human chromosome-1q is linked to microcephaly with agenesis of the corpus callosum (e.g. [9][10][11], and a critical region contains only a handful of genes, including RP58. 9-12 RP58, also known as ZNF238, 13 encodes a transcription factor with a BTB/POZ and four zincfinger domains 14 that is highly conserved (495%) between humans and mice, suggesting conserved functions.…”
mentioning
confidence: 99%
“…4,6,7,9,11,18 After chromosomal microarray testing has been available for the identification of submicroscopic chromosomal aberrations, many patients with submicroscopic deletions of 1q44 have been identified. 8,10,12,14,15 Now, precise genotype-phenotype correlation has been evaluated through the accumulation of patients with variable deletion sizes, and a minimal essential region has been proposed for expressing the main characteristics of 1q44 deletion syndrome. 7,8,[14][15][16] Ballif et al 17 evaluated 22 patients with small interstitial deletions of 1q44 and demonstrated critical regions for microcephaly, ACC and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,12,14,15 Now, precise genotype-phenotype correlation has been evaluated through the accumulation of patients with variable deletion sizes, and a minimal essential region has been proposed for expressing the main characteristics of 1q44 deletion syndrome. 7,8,[14][15][16] Ballif et al 17 evaluated 22 patients with small interstitial deletions of 1q44 and demonstrated critical regions for microcephaly, ACC and seizures. Consequently, AKT3 was reported to be the gene responsible for microcephaly; zinc finger protein 238 gene (ZNF238) for ACC; and heterogeneous nuclear ribonucleoprotein U gene (HNRNPU) for seizures 17 ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation